O direito à adaptação climática na sociedade urbana de risco : gestão climática para os municípios brasileiros - Melo, Tibério Bassi de (Universidade do Vale do Rio dos Sinos, 2024)
The present thesis proposes a new right in response to one of the greatest current concerns: the lack of security for a significant number of Brazilians living in vulnerable situations in urban areas, without the guarantee of the right to the city. As a result, they are more exposed to the risks imposed by climate change, due to the increased frequency and magnitude of extreme natural events. The mitigation of these events is already being pursued through global climate change policies aimed at reducing greenhouse gas emissions. However, these events are inevitable because they are natural, but this does not preclude preventive adaptation actions that aim to build resilience against them. The general objective of this thesis was to address the issue of guaranteeing the right to the city for people in conditions of urban, environmental, and climate risk due to the escalation of the climate crisis and the increase in extreme climate events. The specific objectives were to observe the evolution of the urban phenomenon as a global phenomenon and the evolution of the urban crisis in Brazil, which has generated numerous social injustices and greater exposure to risks. It also involved observing the advance of the climate crisis, which is deepening the risk society and inaugurating a new geological era, the Anthropocene, characterized by catastrophic environmental and climate disasters. Finally, the thesis examined the responses of the legal system to environmental and climate crises, both of an international nature—stemming from multilateral international agreements—and from the national legal system, in relation to urban and climate crises. The conclusions pointed to the fact that recognizing a right to climate adaptation is essential to guaranteeing the right to the city, human dignity, and urban, environmental, and climate sustainability. The method used is pragmatic systemic, observing intersystemic communication and network relationships, with the technique of qualitative and exploratory bibliographic research, which included various American authors due to the development of the subject by the increased occurrence of extreme and catastrophic climate events in that country.
Keywords: Fenômeno urbano; Crise urbana; Crise climática; Antropoceno; Injustiças; Vulnerabilidades e adaptação climática; Urban phenomenon; Urban crisis; Climate crisi; Anthropocene; Injustices; Vulnerabilities and climate adaptation; ACCNPQ::Ciências Sociais Aplicadas::Direito